Research of infusion therapy: to advance knowledge & improve practice - Daud, Azlina (2020)
Research of Infusion Therapy: To advance knowledge & improve practice. Selection of the right device and the right inserter encompasses the second stage of the VHP process. Appropriate device selection and number of necessary lumens is a determination made according to lowest risk for patient insertion and potential for infection in conjunction with the needs of the therapy. Selection of the inserter and application of infection prevention principles are contributing factors for patient safety. Vascular access specialists and teams of specially trained clinicians function to aid in selection and insertion of the most appropriate device. Ensuring the insertion is performed by a trained and qualified clinician with ultrasound skills reduces insertion and post insertional complications.